2022
DOI: 10.1039/d2ra01640k
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical synthesis of inorganic cryogel Ag2Mo3O10@Ag/AgO: structural characterization, antibacterial activity, and dye adsorption properties

Abstract: An ultrasonic-assisted synthesis of Ag2Mo3O10@Ag/AgO cryogel (SMSSO) nanocomposite was developed, and a possible formation mechanism of multi-layered SMSSO was proposed based on characterization results of SEM, EDX, XRD, Raman spectroscopy, and DRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Nanocrystal-based cryogels are highly promising novel materials showcasing high surface areas and a porous structure which bridge the gap between the macroscopic scale and the nanoscopic properties of the building blocks. The huge library of options for these building blocks, either regarding on their composition (semiconducting, magnetic, plasmonic or mixtures of them [86] ), their size and shape (nanowires [26,112,118] , nanoplatelets [103,119] , spheres, cubes …) or their surface functionalization, open the possibility to tackle a broad range of societal problems, such as environmental remediation [25,55,120] or energy saving and conversion. [15,121] Their superior performance in several applications such as electro-or photocatalysis in comparison to the colloidal counterpart has been extensively proven, [21,85,87,110] being possible to obtain better catalysts with lower loads of noble metals, which decrease considerably the price and overcome the problem of the scarcity of these elements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanocrystal-based cryogels are highly promising novel materials showcasing high surface areas and a porous structure which bridge the gap between the macroscopic scale and the nanoscopic properties of the building blocks. The huge library of options for these building blocks, either regarding on their composition (semiconducting, magnetic, plasmonic or mixtures of them [86] ), their size and shape (nanowires [26,112,118] , nanoplatelets [103,119] , spheres, cubes …) or their surface functionalization, open the possibility to tackle a broad range of societal problems, such as environmental remediation [25,55,120] or energy saving and conversion. [15,121] Their superior performance in several applications such as electro-or photocatalysis in comparison to the colloidal counterpart has been extensively proven, [21,85,87,110] being possible to obtain better catalysts with lower loads of noble metals, which decrease considerably the price and overcome the problem of the scarcity of these elements.…”
Section: Discussionmentioning
confidence: 99%
“…This versatile technique is based on the freezing and subsequent solvent crystal evaporation of a gelling solution, which can be polymeric precursors, [22] a mixture of polymer/nanoparticles dispersed in an aqueous solvent, [23,24] a nanoparticle colloid, or a preformed hydrogel. [25,26] The principle of cryogelation is based on the occurrence of a heterophase system at low temperatures, which consists of a solid phase (the ice crystals of the solvent) and another unfrozen liquid microphase (in between the ice crystals) that contains the gelling solutes (Figure 1a). [17] The gelation step can only occur in this liquid microphase.…”
Section: Fabrication and Macro-structuringmentioning
confidence: 99%
“…Ag and Sr are attached to the crystalline scaffold of hydroxyapatite (HA), which, in addition to reducing cytotoxicity, causes the antibacterial properties of this polymer in the long term 105 . Based on a study conducted by Mohammadi et al in 2022 on Ag 2 Mo 3 @Ag/Ag 2 cryogel, it was observed that the synthesized cryogel shows good performance against E. coli and S. aureus 106 …”
Section: Biomedical Applications Of Polymer Gelsmentioning
confidence: 99%
“…105 Based on a study conducted by Mohammadi et al in 2022 on Ag 2 Mo 3 @Ag/Ag 2 cryogel, it was observed that the synthesized cryogel shows good performance against E. coli and S. aureus. 106 Contamination and infection of diabetic wounds with S. aureus and P. aeruginosa can cause a delay in wound healing compared to non-infected wounds. Using PUAO-CPO-EXO cryogel dressing on infected diabetic wounds accelerates wound healing compared to infected wounds of the control group and it was observed that this scaffold can prevent the infection of diabetic wounds.…”
Section: Antibacterial Properties Of Polymer Gelsmentioning
confidence: 99%
“…One of the most important global issues is water pollution and the depletion of freshwater resources, which threatens economic development and ecosystem health [ 1 , 2 ]. Industrial wastewater, particularly dye wastewater, is highly valued because of its high level of pollution and the challenges associated with effective treatment.…”
Section: Introductionmentioning
confidence: 99%